1952
DOI: 10.1172/jci102690
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cardiac Function and Body Composition With Special Reference to Obesity 1

Abstract: It has been known for many years that the surface area is increased with increasing obesity and that this increase in surface area is accompanied by a proportional increase in basal oxygen consumption (1). Therefore, it has been reasoned that in the presence of obesity cardiac output and cardiac work in the basal state are increased approximately in proportion to the increase in oxygen consumption (2). This reasoning is based on the assumption that the quantity of oxygen carried away by a liter of blood from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1952
1952
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…In fact, the formula used by Bae (21) to predict cardiac output features the same term (BW 0.425 3 [100 H] 0.725 ) as the formula used by Du Bois and Du Bois (19) to predict BSA. On the other hand, Taylor et al (30) reported that LBW has a stronger correlation with cardiac output than BSA. LBW is a major predictor of functional capacity in the field of pharmacology (31), and we suggest it as a determinant for the administration of iodinecontaining CM.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, the formula used by Bae (21) to predict cardiac output features the same term (BW 0.425 3 [100 H] 0.725 ) as the formula used by Du Bois and Du Bois (19) to predict BSA. On the other hand, Taylor et al (30) reported that LBW has a stronger correlation with cardiac output than BSA. LBW is a major predictor of functional capacity in the field of pharmacology (31), and we suggest it as a determinant for the administration of iodinecontaining CM.…”
Section: Discussionmentioning
confidence: 98%
“…In subjects with marked obesity and perhaps in those with abnormal fluid retention, the body surface area calculated according to Du Bois and Du Bois (9) might distort the predicted value for cardiac index (10,11). The cardiac output also was expressed in terms of oxygen consumption as a ratio by the formula:…”
Section: Cardiac Outputmentioning
confidence: 99%
“…The cardiac outputs determined by the corrected acetylene method will be presented in detail elsewhere (12).…”
Section: And Analysismentioning
confidence: 99%